Fiscal Multipliers and the Labour Market in the Open Economy - Christian Merkl; Ester Faia; Wolfgang Lechthaler (Verein für Socialpolitik, 2010)
Several contributions have recently assessed the size of fiscal multipliers both in RBC models and New Keynesian models. None of the studies considers a model with frictional labour markets which is a crucial element, particularly at times in which much of the fiscal stimulus has been directed toward labour market measures. We use an open economy model (more specifically a currency area calibrated on the EMU) with labour market frictions in the form of labour turnover costs and workers' heterogeneity to measure fiscal multipliers. We compute short and long run multipliers and open economy spillovers for five types of fiscal packages: pure demand stimuli and consumption tax cuts return very small multipliers; income tax cut and hiring subsidies deliver larger multipliers as they reduce distortions in sclerotic labour markets; short-time work (German Kurzarbeit) returns negative short-run multipliers, but stabilises employment. Our model highlights a novel dimension through which multipliers operate, namely the labour demand stimulus which occurs in a model with non-walrasian labour markets.
Keywords: E62; H30; J20; 330; fiscal multipliers; fiscal packages; labour market frictions